2012
DOI: 10.1016/j.pec.2011.07.025
|View full text |Cite
|
Sign up to set email alerts
|

Family communication as strategy in diabetes prevention: An observational study in families with Dutch and Surinamese South-Asian ancestry

Abstract: Findings favor training of clinicians in utilizing a family approach as prevention strategy. Patients (particularly Surinamese South-Asians) are in need of professional help in the process of family risk disclosure. (Online) Educational tools should be made available at which patients can refer their relatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 34 publications
2
22
0
Order By: Relevance
“…For instance, in the assessment of the migrants at the migration source, we observed that “subjunctive community” (composed by migrants’ social network) [35] and the “key person” play a very important role in the ideas of the group.The researchers purposely arranged for the “key person” to communicate with the HIV-positive migrant, and encouraged them to exploit the “subjunctive community” in peer education. Simultaneously, in rural migration destinations, education is promoted by social and family support.The information exchange and emotional communication among family members has an important effect on individual perceptions, beliefs, and behaviors [36]. Intervention of family members can not only provide migrants with a more powerful support system, but also acts to reduce the possibility of HIV transmission from migrants to their family members.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in the assessment of the migrants at the migration source, we observed that “subjunctive community” (composed by migrants’ social network) [35] and the “key person” play a very important role in the ideas of the group.The researchers purposely arranged for the “key person” to communicate with the HIV-positive migrant, and encouraged them to exploit the “subjunctive community” in peer education. Simultaneously, in rural migration destinations, education is promoted by social and family support.The information exchange and emotional communication among family members has an important effect on individual perceptions, beliefs, and behaviors [36]. Intervention of family members can not only provide migrants with a more powerful support system, but also acts to reduce the possibility of HIV transmission from migrants to their family members.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research shows that people from certain cultural backgrounds may be more likely to discuss familial risk of type 2 diabetes with their relatives [39,41,42]. For example, Surinamese patients expressed more concern about their relatives' risk of diabetes, compared to Dutch patients [41].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research shows that people from certain cultural backgrounds may be more likely to discuss familial risk of type 2 diabetes with their relatives [39,41,42]. For example, Surinamese patients expressed more concern about their relatives' risk of diabetes, compared to Dutch patients [41]. Another study showed that people from Bahrain are less likely to take responsibility to prevent type 2 diabetes and to be influenced by medical advice in comparison to people from Ireland [42].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, professionals are right in stating that the effect of using FH in preventive communications targeting specific populations remains undetermined [10-12]. We only know that in families with different ethnic backgrounds (e.g., South-Asian, Middle-Eastern), family communication about T2D is not a taboo and patients seem willing to pass on risk and preventive information in their family [18,30]. …”
Section: Discussionmentioning
confidence: 99%
“…This means that relatives are reached via the index patient, who informs them about increased familial susceptibility to a disease and the preventive options. Research already has indicated that the majority of patients with T2D seems willing to disseminate risk and preventive information in their family [18,19]. Adult offspring generally appears receptive to be informed about reducing their diabetes risk via the family system [20].…”
Section: Introductionmentioning
confidence: 99%